Gradual reforms and the emergence of energy market in China: Evidence from tests for convergence of energy prices - Ma, H.; Oxley, Leslie; Gibson, J. (Elsevier Science, 2009)
This study investigates the emergence of energy markets by testing for convergence of energy prices with a new dataset on energy spot prices in 35 major cities in China. Both descriptive statistics and unit root are employed to test the convergence of energy prices for each of four fuel price series. The whole study period is divided into two sub-periods in order to reconcile the gradual energy reforms. The results show the steady improvement in energy market performance in China, especially during the second sub-period, which suggests that the market appears to be playing an increasing role in determining energy prices. While panel unit root tests show energy markets are integrated in China as a whole, city-by-city univariate unit root tests suggest that there are still many regional energy markets, probably because energy reserves (especially coal) vary widely across regions. Since China's energy economy is gradually moving towards market-oriented mechanisms, the existing literature may become obsolete soon. © 2009 Elsevier Ltd. All rights reserved.